Wildlife migration in Ethiopia and South Sudan longer than ‘the longest in Africa’: a response to Naidoo et al. - Schapira, P; Monica, M; Rolkier, G; Bauer, H (Cambridge University Press, 2016)
Naidoo et al. (2016) reported a 500 km round-trip zebra Equus quagga migration as A newly discovered wildlife migration in Namibia and Botswana is the longest in Africa. Their paper is interesting but their claim is incorrect, as demonstrated by the evidence presented here of a substantially longer terrestrial mammalian migration.